Sonographic characteristics of pilomatricomas and their association with symptom duration. Issue 40 (2nd October 2020) - Hosokawa, Takahiro; Shibuki, Saki; Tanami, Yutaka; Sato, Yumiko; Oguma, Eiji
Abstract : Abstract: This study aimed to investigate the associations between the sonographic findings and duration of symptoms in children with pilomatricoma. This study included 86 children with 95 lesions confirmed to be pilomatricoma after pathological examination. The associations between symptom duration and sonographic observations, including the presence or absence of peritumoral hyperechogenicity, calcification, and vascularity were investigated. The internal echogenicity of each pilomatricoma was scored using a 5-point scale based on echogenic spots and calcification with posterior acoustic shadowing. The Mann–Whitney U and Kruskal–Wallis tests were used for statistical analysis. We found that the absence of peritumoral hyperechogenicity and severity of calcification were associated with increased symptom duration. Calcification, (present, 19.19 ± 18.99 months vs absent, 4.31 ± 3.24 months; P < .01) and peritumoral hyperechogenicity (present, 5.02 ± 5.80 months vs absent, 16.17 ± 18.24 months; P < .01), and grade of internal echogenicity (grade 0/1/2/3/4 = 3 months [1 patient]/4.33 ± 3.26 months [range, 1–12]/4.57 ± 3.46 months [range, 2–12]/10.89 ± 9.17 months [range, 3–28]/35.27 ± 19.16 months [range, 9–60], respectively; P = .01 and <.01) were associated with significant differences in symptom duration. There were no significant between-group differences in vascularity (6.01 ± 7.24 months; range, 1–48 vs 15.50 ± 19.12 months; range, 1–60; P = .08). Pilomatricomas with a relatively short symptom duration were more likely to exhibit peritumoral hyperechogenicity and calcification with less severe posterior acoustic shadowing compared to lesions with a longer symptom duration. These sonographic findings provided useful information that facilitated the correct and rapid diagnosis of pilomatricoma.